Lignosus rhinocerus attenuates non-alcoholic fatty liver induced by plant-based high-fat diet in hamster - Tsai, Wen-Che; Hoe, Teck-Loong; Lu, Shao-Chun; Kao, Tzu-Chien; Yin, Hsin-Yi; Liao, Jiunn-Wang; Wen, Hsiao-Wei (Electronic Journal of Biotechnology, 2022)
[Display omitted] Non-alcoholic fatty liver disease (NAFLD) is the most common liver disorder globally, and is often caused by abnormal fatty acid metabolism. Plant-based fatty acid may lower the risk of NAFLD, but evidence shows that plant-based fatty acid can still induce fatty liver. Lignosus rhinoceros is a mushroom that is widely used as folk medicine in Southeast Asia. Studies indicate that L. rhinoceros can act as an antioxidant and immune modulator, might be a potent modulator for NAFLD. In this study, a plant-based high-fat diet (HFD) was used to induce fatty liver in hamsters. Hot water extract of L. rhinoceros was applied during the induction period. The antioxidant capacity of L. rhinoceros was evaluated. Data reveal that L. rhinoceros extract had promising DPPH scavenging and ferrous ion chelating compacities. The total phenolic and flavonoid contents were 366.23 ± 5.06 mg gallic acid and 28.67 ± 2.5 mg rutin equivalents per gram of raw L. rhinocerus powder, respectively. Lignosus rhinoceros extract lowered body weight, and reduced liver damage which was induced by HFD in hamster, possibly by reducing mononuclear cell infiltration in the liver. Lignosus rhinoceros treatment also lowered the cholesterol content and improved the HDL-c/LDL-c level in hamster serum. Finally, L. rhinoceros reduced the reactive oxygen species content in the liver which was caused by HFD. This investigation provides evidence that a plant-based HFD may be a risk factor in fatty liver. It also proves that L. rhinoceros promotes liver health, and so can be used in functional food. How to cite: Tsai W-C, Hoe T-L, Lu S-C, et al. Lignosus rhinocerus attenuates non-alcoholic fatty liver induced by plant-based high-fat diet in hamster. Electron J Biotechnol 2022;58. https://doi.org/10.1016/j.ejbt.2022.05.004.